Development of Guided Writing Teaching Materials Based on High Order Thinking Skills for Grade VI Elementary School Students - Meidias Abror Wicaksono; Ida Zulaeha; Panca Dewi Purwati; Meidias Abror Wicaksono; Ida Zulaeha (Universitas Negeri Malang, 2025)
This study aims to develop guided writing teaching materials based on High Order Thinking Skills (HOTS) with the 4-D development research model approach (Define, Design, Develop, Disseminate). The development process begins with the define stage to identify student needs and analyze the curriculum, followed by the design stage to design the initial teaching materials. At the develop stage, the teaching materials were validated by media experts and material experts, and tested on 28 students of grade VI state elementary school 01 Wates Semarang. The last stage, disseminate, was conducted to disseminate the product openly to teachers and students in the context of learning. The results showed that validation from media experts resulted in an average score of 90.5% (very feasible category), while validation from material experts resulted in an average score of 92% (very feasible category). The trial of the developed teaching materials to 28 elementary school students of grade VI state elementary school 01 Wates in Semarang City and the results of the comparison between pretest and posttest were -4.543, with a p value (Asymp. Sig.) of 0.000 (p < 0.05) with an effective category of improving students' writing skills by providing stimulation to think critically, analytically, and creatively according to HOTS characteristics. Thus, the development of HOTS-based writing teaching materials can be an effective innovation in literacy learning in elementary schools, especially to improve in-depth and meaningful guided writing skills. This study recommends wider implementation of this teaching material in other classes as well as further development based on digital technology to reach a wider audience.